The sexual and reproductive health needs, experiences and challenges faced by women in Saudi Arabia from stakeholders’ perspectives - Alomair, Noura; Alageel, Samah; Davies, Nathan; Bailey, Julia V. (Frontiers in Global Women's Health, 2025)
The perceptions, beliefs, and experiences of Muslim women regarding sexual and reproductive health are influenced by numerous factors. This study explores the sexual and reproductive health needs and challenges faced by women in Saudi Arabia, drawing on insights from key professional stakeholders. It examines the challenges faced by Saudi women and the obstacles they encounter in accessing healthcare services from the perspectives of stakeholders.MethodsThe study employed a qualitative design using semi-structured one-on-one interviews with healthcare professionals, policymakers, and religious scholars in Riyadh, Saudi Arabia. The data were analysed using reflexive thematic analysis. Participants were recruited using purposive sampling.ResultsThe professional stakeholder sample included 16 participants: seven healthcare providers, six policymakers, and three religious scholars. The data revealed widespread gaps in women's sexual and reproductive health knowledge, including misconceptions about menstruation, reproduction, contraception, and sexual function. Participants described how cultural taboos and restrictive social norms foster negative attitudes toward sex and sexuality, which contribute to misinformation, fear, and sexual dysfunction. Women's ability to seek information or express sexual needs was often limited by expectations of modesty, with sexual awareness perceived as inappropriate or shameful. Stakeholders highlighted childhood sexual abuse as a prevalent yet silenced issue, with lasting effects on sexual health and well-being. Stakeholders emphasised the importance of improving sexual health education, promoting public awareness, and encouraging open, culturally sensitive dialogue to support sexual and reproductive health.ConclusionThis study highlights the impact of societal taboos and cultural beliefs on women's sexual and reproductive experiences. The study emphasises the need for improved education, greater public awareness, and open communication to address misconceptions and support women's well-being. Promoting women's sexual well-being includes creating a more informed, inclusive, and supportive environment for women's sexual and reproductive health and advocating for policies that protect and promote their sexual and reproductive health.